Novel Haplotype Indicator for End-Stage Renal Disease Progression among Saudi Patients - Cyril Cyrus; Shahanas Chathoth; Chittibabu Vatte; Nafie Alrubaish; Othman Almuhanna; J. Francis Borgio; Samir Al-Mueilo; Fahd Al Muhanna; Amein K. Al Ali (International Journal of Nephrology)
Background. End-stage renal disease (ESRD) is the result of hypertensive nephrosclerosis and chronic glomerular diseases and is associated with high morbidity and mortality. There are strong heritable components in the manifestation of the disease with a genetic predisposition to renal disorders, including focal segmental glomerulosclerosis and arterionephrosclerosis. Recent studies in genetics have examined modifiable risk factors that contribute to renal disease, and this has provided a deep insight into progressive kidney disease. Single-nucleotide polymorphisms at the proximity of SHROOM3, CST3, SLC7A9, and MYH9 genes have been associated with an increased risk of developing CKD and ESRD. Methods. A total of 160 CKD patients and 189 control subjects of Saudi origin participated in the study. Eight polymorphisms (SHROOM3-rs9992101, rs17319721; SLC7A9-rs4805834; MYH9-rs4821480, rs4821481, rs2032487, rs3752462; CST3-rs13038305) were genotyped using TaqMan assay, and the haplotype analysis was done using the HaploView 4.2 software. Results. Haplotype analysis revealed a novel haplotype “E6”-GTTT to be associated significantly with an increased risk for ESRD (p=0.0001) and CKD (p=0.03). Conclusion. CKD is often silent until symptomatic uremia during the advanced stages of the disease. The newly identified haplotype will help recognize patients at risk for a rapid progression of CKD to ESRD. Accurate detection and mapping of the genetic variants facilitates improved risk stratification and development of improved and targeted therapeutic management for CKD.